PENGARUH INFLASI, SUKU BUNGA, DAN NILAI TUKAR RUPIAH (KURS) TERHADAP INDEKS LQ-45 DI BURSA EFEK INDONESIA PERIODE 2011 – 2023 - Fakhri Ammar, Muhammad; Intan Sari, Widya (Journal of Research and Publication Innovation, 2024)
This research was conducted with the aim of determining the influence of inflation, Interest Rates, and the Rupiah Exchange Rate (Kurs) on the LQ-45 Stock Price Index on the Indonesian Stock Exchange for the period 2011 – 2023. The research method in this research is quantitative research. The type of sampling is purposive sampling with criteria determined by the author. The data used is time series data for the period January 2011 to December 2023. The data analysis technique uses multiple linear regression analysis with a significance level of 5%. Based on the partial test results, the Inflation variable has a positive and insignificant influence on the LQ-45 Stock Price Index, the Interest Rate variable partially has a negative and insignificant influence on the LQ-45 Stock Price Index, and the Rupiah Exchange Rate (Exchange Rate) variable partially has a positive and significant influence on the LQ-45 Stock Price Index. Meanwhile, simultaneously it was found that there was a significant positive influence between inflation, interest rates and the Rupiah exchange rate (exchange rate) on the LQ-45 share price index on the Indonesian Stock Exchange.